2001
DOI: 10.1614/0890-037x(2001)015[0112:wminaw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Weed Management in Narrow- and Wide-Row Glyphosate-Resistant Soybean (Glycine max)1

Abstract: Field experiments were conducted over 3 yr at three locations in Illinois to evaluate the efficacy of glyphosate in glyphosate-resistant soybean planted in rows spaced 19, 38, and 76 cm. Minimal soybean injury (less than 10%) was observed from any glyphosate treatment. Glyphosate treatments controlled 82 to 99% of giant foxtail. Common waterhemp control was increased as soybean row spacing was decreased. Applying sequential glyphosate applications or increasing the glyphosate rate from 420 g ae/ha to 840 g/ha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 10 publications
(12 reference statements)
6
57
0
Order By: Relevance
“…Despite the lack of differences in some site-years, trends across the other site-years were consistent and show that offlabel (beyond 6L) applications in the GR system can have substantial effects on crop yield and yield components, resulting in significant declines in the income derived from GR canola crops. Our results are perhaps not surprising given that delayed herbicide applications to other HR crops (soybean, cotton, corn) caused reduced growth (Norsworthy 2004;Pline et al 2003;Young et al 2001), altered reproductive morphology, male sterility, and reductions in seed set (Pline et al 2002a,b;Thomas et al 2004).…”
Section: Resultsmentioning
confidence: 58%
“…Despite the lack of differences in some site-years, trends across the other site-years were consistent and show that offlabel (beyond 6L) applications in the GR system can have substantial effects on crop yield and yield components, resulting in significant declines in the income derived from GR canola crops. Our results are perhaps not surprising given that delayed herbicide applications to other HR crops (soybean, cotton, corn) caused reduced growth (Norsworthy 2004;Pline et al 2003;Young et al 2001), altered reproductive morphology, male sterility, and reductions in seed set (Pline et al 2002a,b;Thomas et al 2004).…”
Section: Resultsmentioning
confidence: 58%
“…Sequential applications have provided greater and more consistent weed control than have single applications (Wait et al 1999;Payne and Oliver 2000;Wiesbrook et al 2001). However, level of weed control was dependant on time of application of single treatments and on crop row width, with Abbreviations: CHU, corn heat unit 1199 greater control at narrow-row spacings (Ateh and Harvey 1999;Young et al 2001). Soybean yield is affected by level and time of removal of weed competition.…”
Section: Ivany J a 2004 Comparaison Des Méthodes De Lutte Contre mentioning
confidence: 99%
“…Young et al [30] observed that the reduction in row spacing from 76 cm to 38 cm, increased weed control after herbicide application. In contrast, glyphosate presented weed control superior to 90% at row spacing of 19 cm, controlling between 75% and 90% of the weeds when crop was planted at a spacing of 76 cm.…”
Section: Soybean Plants Arrangement and Its Relationship With Weedsmentioning
confidence: 99%